Analyse des représentations de professionnels impliqués dans deux parcours de sujets dits « incasables » - Gillonne Desquesnes; Nadine Proia-Lelouey; Didier Drieu (Sociétés et Jeunesses en Difficulté)
This paper examines the first results of a research about institutional trajectories of multiproblem young people. Based on files and semi-structured interviews of professionals, we reassemble the elements of two different trajectories in child protection. We sketch a portrait of the troubles presented by two different youngsters and their home environment. We review each of the child protection measures that form chaotic and complex trajectories. The results show both an accumulation of negative events in the life of these two youngsters and an accumulation of malfunctions of the institutions of which the consequences are a sequel of problems. Although the two subjects present troubles which have things in common with the antisocial personality disorder, we wonder about the inability of professionals to classify these subjects in this psychopathological frame that might allow them to understand the problem they are confronted with. Finally we question the connection between educational and psychiatric institutions. Each of these two institutions tends to reject theses youngsters because they consider them as out of their skills. We elaborate the idea that the educational institution might care efficiently for them, if the containing function of health professionals, who would maintain supervision systems in order to protect the team of the attacks of the youngsters, was provided.